Internal herniation of Meckel's diverticulum through meso-appendix in infant: An extremely rare occurrence - Shibsankar Barman; Md. Hadiuzzaman; Sougata Ray; Ruchirendu Sarkar (Wolters Kluwer Medknow Publications, 2016)
Intestinal obstruction due to internal herniation is rare. There is only 0.5-5.8% of incidence described in the available literature. In infancy, it is rarer. Internal herniation of Meckel's diverticulum through meso-appendix in an infant is an extremely rare emergency situation, and probably the first case to be reported in the literature.